2022
DOI: 10.1007/s40489-022-00340-8
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Anxiety Among Parents of Transition-Aged Children with Autism Spectrum Disorder: a Systematic Review of Interventions and Scales

Abstract: The period between adolescence to young adulthood can be stressful for parents of transition-aged children (14 to 22 years old) with autism spectrum disorder. A systematic review was undertaken to examine if existing interventions address the unique parental stressors of this phase and if the scales used to measure parental stress and anxiety are suitable for this group. Of the 9813 studies screened, only 13 studies met the inclusion criteria. Findings indicated that interventions focused on mindfulness, socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 123 publications
0
11
0
Order By: Relevance
“…Indeed, several studies suggested that growing up in a family with an autistic person could lead to a greater burden of responsibility, as well as concerns about the future of the sibling and the role that will have to be assumed in the future once the parents will not be able to assist the affected sibling or after their loss [19,23,[66][67][68][69][70]. Non-autistic siblings of autistic people could also prevail feelings of frustration dictated by the perception of a greater parental attention toward the affected sibling, due to the numerous needs of the autistic child, as well because of the possible burden of parental distress [66,67,71,72].…”
Section: Behavioral Attitudes and Associated Factorsmentioning
confidence: 99%
“…Indeed, several studies suggested that growing up in a family with an autistic person could lead to a greater burden of responsibility, as well as concerns about the future of the sibling and the role that will have to be assumed in the future once the parents will not be able to assist the affected sibling or after their loss [19,23,[66][67][68][69][70]. Non-autistic siblings of autistic people could also prevail feelings of frustration dictated by the perception of a greater parental attention toward the affected sibling, due to the numerous needs of the autistic child, as well because of the possible burden of parental distress [66,67,71,72].…”
Section: Behavioral Attitudes and Associated Factorsmentioning
confidence: 99%
“…As families provide the foundation of long-term care for those with ASD, it is imperative to adequately support them. Yet, a recent systematic review of interventions to mitigate stress and anxiety among caregivers of ASD youth identified only two studies, out of the 13 available, that focused specifically on caregivers of transition-age youth [ 52 ]. Furthermore, while numerous interventions exist that train typically developing siblings as therapy agents (e.g., siblings teach, model, or prompt) to improve ASD youth's social or behavioral skills, far fewer interventions have been developed to address siblings' psychosocial needs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent systematic review indicated that scales estimating parenting stress are often improperly implemented and do not accord with the group studied [27]. Among these scales, the Parenting Stress Index (PSI), designed for parents of children between 3 months and ten years old, has been utilized among parents of children with disabilities and those older than the recommended age range [27].…”
Section: Measurements Of Parenting Stress In Asdmentioning
confidence: 99%
“…However, a recent systematic review indicated that scales estimating parenting stress are often improperly implemented and do not accord with the group studied [27]. Among these scales, the Parenting Stress Index (PSI), designed for parents of children between 3 months and ten years old, has been utilized among parents of children with disabilities and those older than the recommended age range [27]. This could cause problems as the scale may not capture the unique factors impacting stress levels in parents raising a child with a disability or ASD, while also not capturing the stressors associated with the child's respective age.…”
Section: Measurements Of Parenting Stress In Asdmentioning
confidence: 99%
See 1 more Smart Citation